SUMMATIVE ASSESSMENT OF TENTH-GRADE ENGLISH TEACHERS FROM HOTS PERSPECTIVE - Anggita Prasistha Utami; Eka Sulistia Dewi; Gede Yudha Paramartha (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
This research intends to analyze how Higher Order Thinking Skills are reflected in summative assessment used by Tenth-grade English teachers from HOTS perspective based on Revised Bloom's Taxonomy. This research used qualitative research with a content analysis method to know the extent of HOTS items that are reflected in the teacher-made test. To collect the data, document analysis and interviews were applied. From the data that have been obtained, it was found out that the HOTS-based item used by the teachers was still relatively low. There were only 6 out of 125 items that can be categorized as HOTS-based items with a percentage of 4.8%. HOTS-based items that have been found were also limited to the Analyze category (C4). In the C4 level, three indicators or sub-skills were included such as differentiating, organizing, and attributing. Among six HOTS-based items, 2 items were categorized as differentiating indicators, 1 item belonged to the organizing indicator, and 3 items were attributing indicator. Furthermore, the result of the interview indicated that the teachers need to learn more about HOTS to get a better understanding in constructing HOTS-based items.